Evaluating naturalness of voice impersonations by subjective and objective measures - Ng, Chen Yi. (2013)
This project is to find out the reasons why some impersonated voices is able to deceive people and whether it is possible to quantify the voices. As there is a rise in crimes related to voice impersonation, it is important to know how a person changes his/her voice to another person’s voice and what are the factors which a human determines whether the voice is disguised or not. Subjective and objective measure is used for this project.